Trust, sociability and stock market participation - Dimitris Georgarakos; Giacomo Pasini (Goethe University Frankfurt, Center for Financial Studies (CFS), 2009)
We investigate the effects of both trust and sociability for stock market participation, the role of which has been examined separately by existing finance literature. We use internationally comparable household data from the Survey of Health, Ageing and Retirement in Europe supplemented with regional information on generalized trust from the World Value Survey and on specific trust to financial institutions from Eurobarometer. We show that trust and sociability have distinct and sizeable positive effects on stock market participation and that sociability is likely to partly balance the discouragement effect on stockholding induced by low generalized trust in the region of residence. We also show that specific trust in advice given by financial institutions represents a prominent factor for stock investing, compared to other tangible features of the banking environment. Probing further into various groups of households, we find that sociability can induce stockholding among the less well off in Sweden, Denmark, and Switzerland where stock market participation is widespread. On the other hand, the effect of generalized trust is strong in countries with limited participation and low average trust like Austria, Spain, and Italy, offering an explanation for the remarkably low participation rates of the wealthy living therein.
urn:nbn:de:hebis:30-73593
Keywords: A13; D12; D8; G11; 330; Trust; Sociability; Household Finance; Stockholding; Anlageverhalten; Wertpapieranlage; Aktie; Soziale Beziehungen; Vertrauen; Anlageberatung; Schätzung; Europa